2015
DOI: 10.1021/cm502998w
|View full text |Cite
|
Sign up to set email alerts
|

Raman Detected Sensing of Volatile Organic Compounds by Vapochromic Cu[AuX2(CN)2]2 (X = Cl, Br) Coordination Polymer Materials

Abstract: Two vapochromic coordination polymers Cu-[AuX 2 (CN) 2 ] 2 (X = Cl, 1; X = Br, 2) were prepared and spectroscopically characterized. Exposure of these solid materials to the volatile organic compounds dimethylformamide (DMF), dimethyl sulfoxide (DMSO), pyridine, 1,4-dioxane, and ethylene glycol (glycol) resulted in distinct color, and IR and Raman changes. The thermal stability of the analyte-bound materials was assessed by thermogravimetric a n a l y s i s . S i n g l e -c r y s t a l s t r u c t u r e s o f … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 93 publications
0
23
0
Order By: Relevance
“…Taking the Raman and emission data together, there are four distinct species observed in the degassing of an ammonia‐saturated sample of ZnPt(CN) 4 (Scheme ): a saturated species termed Zn(NH 3 ) 2.5+ y Pt(CN) 4 , the blue‐emitting Zn(NH 3 ) 2.5 Pt(CN) 4 , the cyan‐emitting Zn(NH 3 ) x Pt(CN) 4 (that is not observable by Raman), and ammonia‐free ZnPt(CN) 4 . It is worth noting that this illustrates the utility of the ν CN bands in cyanometallate‐based coordination polymers to monitor the coordination of ligands …”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Taking the Raman and emission data together, there are four distinct species observed in the degassing of an ammonia‐saturated sample of ZnPt(CN) 4 (Scheme ): a saturated species termed Zn(NH 3 ) 2.5+ y Pt(CN) 4 , the blue‐emitting Zn(NH 3 ) 2.5 Pt(CN) 4 , the cyan‐emitting Zn(NH 3 ) x Pt(CN) 4 (that is not observable by Raman), and ammonia‐free ZnPt(CN) 4 . It is worth noting that this illustrates the utility of the ν CN bands in cyanometallate‐based coordination polymers to monitor the coordination of ligands …”
Section: Resultsmentioning
confidence: 77%
“…Cyanometallate‐containing coordination polymers make excellent candidates for chemical vapor sensors, since they are robust and there are many examples of vapochromic and vapoluminescent species . Many of these utilize cyanometallates with close d 10 –d 10 or d 8 –d 8 metal distances (especially between Au I or Pt II centers)—referred to as being metallophilic—since such materials often display emissive behavior .…”
Section: Introductionmentioning
confidence: 99%
“…Complexes of metal dicyanides can be used in the preparation of semiconductor, optically and magnetically active materials [1][2][3][4][5][6][7], drugs-metabolites based on Au(I) [8], and luminescent substances [4,[9][10][11][12]. Complexes of dicyanodihalogenoaurates with various cations, which also exhibit similar properties [13][14][15], are less studied. Several Au(I) cyanide complexes [16,17] and Au(III) cyanodihalide complexes with ammonium cations [18][19][20][21] are known; information on [Cat] + [Au(CN) 2 Hlg 2 ]complexes with organoelement cations is present only in two papers [22,23].…”
Section: Doi: 101134/s1070363221110086mentioning
confidence: 99%
“…PMs which exhibit luminescent chromism in response to exposure to vapors of volatile organic compounds (VOCs), especially, are attractive materials for detecting a small amount of leakage of toxic or explosive gases and for security ink. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] However, these compounds possess potential instability toward the air, moisture, and/or other harsh chemical conditions, and therefore a growing number of studies have recently reported chemically and physically stable PMs. [32,33] Nonporous molecular crystals (NMCs), on the other hand, have no such functional voids in their packing patterns because of the absence of the polymeric or supramolecular structures derived from continuous valence, coordination, or hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…The physical properties of PMs depend drastically on the existence and absence, size, and electronic nature of guests. PMs which exhibit luminescent chromism in response to exposure to vapors of volatile organic compounds (VOCs), especially, are attractive materials for detecting a small amount of leakage of toxic or explosive gases and for security ink [17–31] . However, these compounds possess potential instability toward the air, moisture, and/or other harsh chemical conditions, and therefore a growing number of studies have recently reported chemically and physically stable PMs [32,33] …”
Section: Introductionmentioning
confidence: 99%